2015
DOI: 10.3906/vet-1412-13
|View full text |Cite
|
Sign up to set email alerts
|

Estimating allele frequencies of some hereditary diseases in Holstein cattlereared in Burdur Province, Turkey

Abstract: The economics of dairy cattle breeding around the world has been significantly affected by the autosomal recessive hereditary diseases of bovine leukocyte adhesion deficiency (BLAD), factor XI deficiency (FXID), bovine citrullinemia (BC), and deficiency of uridine monophosphate synthase (DUMPS). The aim of this study was to determine BLAD, FXID, BC, and DUMPS alleles in Holstein cattle raised in Burdur Province in Turkey. This study involved taking blood samples randomly from 500 head of Holstein cattle at var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
6
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 17 publications
4
6
0
Order By: Relevance
“…In Turkey, FXID carrier frequency studies have been conducted in diverse regions. In the Bursa region (Oner et al 2010), carrier frequency of 1.17% was found, in the Burdur region it was 1.8% (Korkmaz Ağaoğlu et al 2015), and in the Thrace region no FXID carriers were found (Avanus & Ahmet 2016), as in the present study. However, for FXID, besides the number of animals sampled, the choice of random or deliberate selection criteria may also be related to the variability in FXID prevalence rates between different countries.…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…In Turkey, FXID carrier frequency studies have been conducted in diverse regions. In the Bursa region (Oner et al 2010), carrier frequency of 1.17% was found, in the Burdur region it was 1.8% (Korkmaz Ağaoğlu et al 2015), and in the Thrace region no FXID carriers were found (Avanus & Ahmet 2016), as in the present study. However, for FXID, besides the number of animals sampled, the choice of random or deliberate selection criteria may also be related to the variability in FXID prevalence rates between different countries.…”
Section: Discussionsupporting
confidence: 76%
“…Whereas the reported carrier frequency in the USA was 0.3% (Robinson et al 1993), it was 13% in Australia, the highest reported prevalence (Healy 1996). Generally, carrier frequencies are very low, as in the case of China with 0.16% (Li et al 2011), or null as we found here, which was also reported in Germany (Grupe et al 1996), Czech Republic (Citek et al 2006), India (Patel et al 2006), and Turkey (Korkmaz Ağaoğlu et al 2015). While the FXID, BC, BLAD, and CVM related alleles have been reported in various countries, in Mexico there are no previous studies of these mutations, except a single study for BLAD (Riojas Valdés et al 2009).…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…No DUMPS and BC carriers were identified in Turkey so far Akyuz & Kul, 2009;Meydan et al, 2010;Oner et al, 2010;Kulaklı & Akyuz 2011;Karslı et al, 2011;Sahin et al 2013;Korkmaz Agaoglu et al, 2015;Kaya et al, 2016).…”
Section: The Prevalence Of Carriers Of Holstein Inherited Diseases Inmentioning
confidence: 99%
“…No DUMPS and BC carriers were identified in Turkey so far Akyuz & Kul, 2009;Meydan et al, 2010;Oner et al, 2010;Kulaklı & Akyuz 2011;Karslı et al, 2011;Sahin et al 2013;Korkmaz Agaoglu et al, 2015;Kaya et al, 2016).…”
Section: The Prevalence Of Carriers Of Holstein Inherited Diseases In Turkeymentioning
confidence: 99%